دور التعليم الإلكتروني في تنمية المهارات الرقمية لدى أعضاء هيئة التدريس بجامعة الأمير سطام بن عبدالعزيز - الكليب، أمل بنت عبدالله بن راشد (جامعة بنها - كلية التربية, 2022)
هدف البحث إلى التعرف على دور التعليم الإلكتروني في تنمية المهارات الرقمية لدى أعضاء هيئة التدريس بجامعة الأمير سطام بن عبد العزيز، من خلال التعرف على واقع التعليم الإلكتروني بجامعة الأمير سطام بن عبد العزيز من وجهة نظر أعضاء هيئة التدريس، والتعرف على أبرز الأساليب المستخدمة في التعليم الإلكتروني بجامعة الأمير سطام بن عبد العزيز لتنمية المهارات الرقمية من وجهة نظر أعضاء هيئة التدريس، ولتحقيق أهداف البحث استخدمت الباحثة المنهج الوصفي المسحي لملائمته للبحث الحالي، وتم اختيار عينة البحث بالطريقة العشوائية الطبقية، حيث طبقت الأداة على عينة مكونة من (348) من أعضاء هيئة التدريس بجامعة الأمير سطام بن عبد العزيز بمحافظة الخرج من جميع الأقسام بالجامعة، وتم استخدام الاستبانة كأداة رئيسة للبحث، وأظهرت نتائج البحث ما يلي: 1- تبين أن هناك تباين في آراء أعضاء هيئة التدريس نحو واقع التعليم الإلكتروني بجامعة الأمير سطام بن عبد العزيز، بمتوسطات حسابية تراوحت ما بين (2.93 إلى 3.87)، وهي مؤشرات تقع في الفئة الثالثة الرابعة التي تبين أن موافقة أفراد العينة من أعضاء هيئة التدريس تشير إلى (محايد/ موافق). 2- تبين أن هناك توافق في آراء أعضاء هيئة التدريس نحو درجة استخدام هذه الأساليب، بمتوسطات حسابية تراوحت ما بين (3.50 إلى 4.12)، وهي مؤشرات تقع في الفئة الرابعة التي تبين أن موافقة أفراد العينة من أعضاء هيئة التدريس تشير إلى (موافق). 3- ظهر وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.05≥α) في آراء عينة البحث نحو واقع التعليم الإلكتروني بجامعة الأمير سطام بن عبد العزيز، وكذلك أبرز الأساليب المستخدمة في التعليم الإلكترونية بالجامعة لتنمية المهارات الرقمية باختلاف متغير التخصص الأكاديمي لصالح أعضاء هيئة التدريس من تخصص المواد العلمية. The research aimed at identifying the role of e-learning in developing digital skills of the teaching staff at Prince Sattam bin Abdulaziz University, through identifying the status of e-learning at Prince Sattam bin Abdulaziz University from the teaching staff’s point of view, as well as identifying the most notable methods used in education. To achieve the objectives of the research, the researcher used the descriptive survey method due to its appropriateness to the current research. The research sample was selected through the stratified randomization manner, where the tool was applied to a sample of (348) members of the teaching staff at Prince Sattam bin Abdulaziz University in Al-Kharj Governorate, throughout the university. The questionnaire was used as the research’s main tool. The results of the research have shown the following: 1- It was found that there is a discrepancy in the opinions of the teaching staff, regarding the status of e-learning at Prince Sattam bin Abdulaziz University, with mean averages ranging between (2.93 and 3.87). These indicators fall into the third and fourth category, stating that the approval of the sample members indicates (Neutral/ Agree). 2- It was found that there is a consensus in the opinions of the teaching staff, regarding the use of these methods, with mean averages ranging between (3.50 and 4.12). These indicators fall into the fourth category, stating that the approval of the sample members indicates (Agree). 3- There were statistically significant differences, at (α ≤ 0.05) level, in the opinions of the research sample towards the status of e-learning at Prince Sattam bin Abdulaziz University, as well as the most notable methods, used in e-learning at the university, to develop digital skills according to the variable of academic specialization in the favour of teaching staff, specializing in scientific subjects.
Keywords: التعليم الإلكتروني -- التكنولوجيا الحديثة -- أعضاء هيئة التدريس -- المهارات الرقمية -- الجامعات السعودية